2019
DOI: 10.23887/jjpbs.v8i1.20589
|View full text |Cite
|
Sign up to set email alerts
|

Prinsip Kerja Sama Dalam Interaksi Jual Beli Di Pasar Tradisional Banyuasri Dan Implikasinya Terhadap Pembelajaran Teks Negosiasi

Abstract: Penelitian ini bertujuan untuk mengkaji bentuk pematuhan dan bentuk pelanggaran prinsip kerja sama dalam interaksi jual beli di Pasar Tradisional Banyuasri serta implikasinya terhadap pembelajaran teks negosiasi di kelas X. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Subjek dalam penelitian ini adalah penjual dan pembeli, sedangkan objeknya adalah prinsip kerja sama. Data dikumpulkan menggunakan metode observasi nonpartisipatif dan metode dokumentasi. Data dalam penelitian ini dianalisis secar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Firstly from traditional market Banyuasri that have been researched by Yukti, et al(2017). They found that seller buyer violated all type of maxims that the most occure was maxim quantity.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly from traditional market Banyuasri that have been researched by Yukti, et al(2017). They found that seller buyer violated all type of maxims that the most occure was maxim quantity.…”
Section: Discussionmentioning
confidence: 99%
“…Mustofa (2010) uses discourse analysis in his research. Meanwhile, pragmatics is used by Astuti (2011), Yuniarsih (2011), Yukti (2018), and Habiburrahman & Arahman (2018). Sosiolinguistics is interesting for Dahar (2015) and Sagala & Rezeki (2019) to examine this topic.…”
Section: Introductionmentioning
confidence: 99%